Application Of SQ3R Strategy (Survey, Question, Read, Recite And Review) In Learning Science On Energy Materials In Living Systems - Riswel Asrita; Asmendri (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2022)
This paper is motivated by students' lack of motivation and enthusiasm in learning science, which results in a decrease in science scores. Science learning should ideally activate and encourage students to work scientifically. So far, science teaching at SMP Negeri 11 Sijunjung has used chiefly the lecture and question and answer method. For this reason, it can be formulated how to apply the SQ3R Strategy (Survey, Question, Read, Recite And Review) in science learning on Energy in Living Systems. The purpose of making this paper is to increase the activeness and critical thinking of students by applying the SQ3R (Survey, Question, Read, Recite And Review) strategy in science learning on Energy in Living Systems.SQ3R strategy is a reading strategy that can help and encourage students to better understand what they read. The SQ3R strategy gives students the possibility to learn systematically, effectively, and efficiently in dealing with various teaching materials. The application of the SQ3R strategy in science learning in class VII.1 of SMPN 11 Sijunjung can increase students' interest, motivation and learning outcomes. This is proven by students being active and focused readers so that they can understand the implied and explicit reading content effectively, an increase in students' communication skills, and differences in the average value of learning outcomes that have increased.